Laboratory reform counteracts the WHO hepatitis C elimination strategy in Germany. Issue 12 (22nd August 2019) - Kramer, Jan; Wolffram, Ingmar; Früh, Uli; Bätz, Olaf; Berg, Thomas; Wiegand, Johannes
Abstract: The World Health Organization and the German government have announced an initiative to eliminate chronic hepatitis C until the year 2030. To reach this goal, one important step is adequate screening and detection of so far undiagnosed infections. The most common initial test is anti‐HCV. This parameter was extra‐budgetary reimbursed by statuary healthcare insurances in the past. However, this policy has changed after a nationwide laboratory reform which should reduce the laboratory costs of patients insured in the statuary healthcare insurances. We therefore analysed the impact of the laboratory reform on the order of anti‐HCV tests in 510 656 anonymized patient data sets before and after the initiation of the reform. The number of anti‐HCV tests declined by 9.4% in quarters I‐III 2018 in comparison with the same time period of the year 2017. The number of HBsAg tests declined by 7.4%, indicating that the reduced anti‐HCV laboratory orders are not parameter‐specific, but most likely a surrogate of the intention of the laboratory reform to generally lower the demands of blood samples and laboratory costs. Thus, the scenario is an important example, how political decisions of the medical self‐government influence the screening setting for viral hepatitis: if the current policy is not changed, the laboratory reform directly counteracts the WHO hepatitis C elimination strategy in Germany.